Bacterial pathogens associated with eyeglasses and risks of infection: A cross-sectional study in South-West Nigeria - Seyi Samson Enitan; Okeoghene Marcel Edafetanure-Ibeh; Grace Eleojo Itodo; Michael Olugbamila Dada; Grace Oluwatoyin Mensah-Agyei; Richard Yomi Akele; Stephen Olasebikan Makanjuola; Saratu Omagbemi Ajike; Nwachi Idume Ogbonna; Jamiu Monsur Olalekan (School of Medicine, Universitas Syiah Kuala, 2022)
Ocular infections have been associated with bacterial contamination of eyeglasses. This study assessed bacterial contaminants associated with the eyeglasses of the staff and students of Babcock University, Ilishan-Remo, Ogun State, Nigeria. A total of 100 participants comprising 33 males and 67 females (aged 16-76 years) were recruited for the study after obtained the written informed consents. A structured questionnaire was used to collect the demographic and clinical information. A total of 100 eyeglasses were examined for bacterial contamination using standard bacteriological methods. A one–way analysis of variance (ANOVA) and Tukey–Kramer multiple comparisons test were used to determine the differences between the bacterial loads among the eyeglasses of study participants. We found that the percentage of eyeglass lenses with unacceptable levels of contamination (105CFU/mL) and acceptable levels of contamination were 19% and 46%, respectively. The percentages of eyeglass handles with unacceptable and accepted level of contamination were 49% and 7%, respectively. Most of the isolated bacteria were sensitive to the tested antibiotics. Risk factors associated with bacterial contamination of eyeglasses were exposure to dusty environment, irregular cleaning, and poor compliance with eyeglass care guidelines. Our study further underscores the claim that eyes glasses may serve as potential vehicles for bacteria capable of causing ocular infections.